The study on crossover layouts of multi-layer winding grooves in deep mine hoists based on transverse vibration characteristics of catenary rope. (February 2019) - Peng, Xia; Gong, Xian-Sheng; Liu, Jin-Jun
In a deep mine winding hoist system, the lateral oscillation of the catenary rope is an important evaluation index of orderly rope arrangement and engineering safety. Different boundary excitations will appear when the wire rope winds on symmetrical or asymmetrical grooves, which results in the different dynamic responses of the hoisting system. In this article, the vibration equations of a deep mine hoisting system are established by using the Hamilton principle, and excitation functions of different crossover zone layouts are deduced. The operation curves are introduced to conduct the experiment based on a certain experimental platform. The lateral oscillation of the catenary rope is recorded by high-speed cameras, and an effective image processing method is proposed to obtain the vibration response of a certain point in the catenary rope. The numerical simulations are compared with the experimental results to prove the vibration models derived in this article are valid. The models could provide reliable basis for the grooves type selection in deep mine hoisting.